Incidence and Risk factors of Retinopathy of Prematurity at a tertiary neonatal care unit in eastern Nepal - Dahal, Sonia; Rajbanshi, Lily; Pyakurel, Kumud (Birat Journal of Health Sciences, 2025)
Introduction: Retinopathy of Prematurity (ROP) is a major cause of preventable blindness in preterm infants. This study aims to determine the incidence of ROP and associated risk factors in preterm infants in a tertiary care hospital in Nepal. Methods: A cross-sectional study was conducted over 18 months in NICU. Preterm infants with gestational age ≤34 weeks or birth weight ≤2000 grams were screened for ROP. Maternal and neonatal data were analysed to identify risk factors. Results: A total of 75 preterm infants were screened, with 19 (25.3%) diagnosed with ROP. Infants with ROP had significantly lower gestational ages (mean 30.52 ± 1.5 weeks) and birth weights (mean 1308.94 ± 288.98 grams) compared to those without ROP (mean gestational age 31.94 ± 1.74 weeks, mean birth weight 1646.25 ± 432.29 grams). Prolonged duration of supplemental oxygen (mean 13.47 ± 4.77 days in the ROP group) was also significantly associated with ROP (p=0.001). Mode of delivery was a significant factor, with caesarean delivery more frequent among ROP cases (p=0.016). Other factors, such as APGAR scores, neonatal jaundice, and neonatal sepsis, showed no significant association with ROP. Conclusion: The incidence of ROP was 25.3% with low gestational age, birth weight, and prolonged oxygen use as key risk factors. Early screening is essential for timely intervention in Nepal.